PENGARUH KEPEMIMPINAN, MOTIVASI KERJA DAN REKRUTMEN TERHADAP KINERJA KARYAWAN PADA PT. TUNAS AUTO GRAHA PALEMBANG (SUMATERA SELATAN) - Omar Hendro; Trisniarty Trisniarty; AM. RZ Rahman (Program Magister Manajemen Indo Global Mandiri University, 2020)
This study aims first, analyzing the effect of leadership, motivation and recruitment simultaneously on employee performance at PT. Tuning Auto Graha Palembang. Second, analyzing the effect of leadership, motivation and recruitment simultaneously on employee performance at PT. Tunas Auto Graha Palembang. The population is 140 people and the sample in this study is based on Sugiyono's opinion with an error rate of 5%, totaling 100 respondents / employees. Testing the validity of the instrument through Corrected Item-Total Correlation, Performance Variables (Y), leadership (X1), and motivation (X2) the results of the test are valid. The reliability test results are all reliable variables on the questionnaire. The results of the statistical calculation of the regression equation Y = 15.149 + 0.327.X1 + 0.624.X2 + 0.438.X3 + e. This study concludes first, leadership, motivation, and recruitment together have a positive and significant effect on the performance of the employees of PT Tunas Auto Graha Palembang City. Second, leadership has a positive and significant effect on employee performance. Third, motivation has a positive and significant effect on employee performance. Fourth, recruitment has a positive and significant effect on the performance of the employees of PT Tunas Auto Graha Palembang City